Here's the question you clicked on:

55 members online
  • 0 replying
  • 0 viewing

alyssababy7

  • 3 years ago

Solve the linear equation. 2(x + 6) + 6 = 3(x + 5) + 7 A. {6} B. {-4} C. {12} D. {9}

  • This Question is Closed
  1. Kira_Yamato
    • 3 years ago
    Best Response
    You've already chosen the best response.
    Medals 1

    2(x + 6) + 6 = 3(x + 5) + 7 2x + 12 + 6 = 3x + 15 + 7 18 - 22 = x x = -4 ==> (B)

  2. Not the answer you are looking for?
    Search for more explanations.

    • Attachments:

Ask your own question

Sign Up
Find more explanations on OpenStudy
Privacy Policy